Composition, cured product, and metal base substrate

JP7644137B2Active Publication Date: 2025-03-11DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022555447
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-06
Filing Date
2021-10-01
Publication Date
2025-03-11
Estimated Expiration
2041-10-01

AI Technical Summary

Benefits of technology

【0009】 本発明の一側面によれば、高温又は高温高湿度環境下での高電圧に対する絶縁信頼性に優れる金属ベース基板を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644137000004
    Figure 0007644137000004
  • Figure 0007644137000005
    Figure 0007644137000005
  • Figure 0007644137000001
    Figure 0007644137000001
Patent Text Reader

Abstract

A composition comprising: an inorganic filler; and a copolymer having a (meth)acrylic monomer unit A having an anionic group, a (meth)acrylic monomer unit B having a cationic group, and a (meth)acrylic monomer unit C other than the (meth)acrylic monomer unit A and the (meth)acrylic monomer unit B, wherein the contained amount of the copolymer is 0.01-10 parts by mass with respect to 100 parts by mass of the inorganic filler.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composition, a cured body, and a metal-based substrate. [Background technology]

[0002] Inorganic fillers formed of boron nitride, aluminum nitride, aluminum oxide, silicon nitride, silicon oxide, etc. are used in various fields for the purpose of improving insulation properties, thermal conductivity, etc. In such cases, the inorganic fillers are generally used by being dispersed in a resin, etc.

[0003] As a more specific example, inorganic fillers may be used in compositions for forming an insulating layer in a metal-based substrate (metal-based circuit substrate). For example, Patent Document 1 discloses a composition for circuit substrates, which contains a specific epoxy resin, a curing agent, and an inorganic filler as essential components, for the purpose of providing a composition made of a curable resin containing an inorganic filler having a low elastic modulus and excellent adhesion, heat resistance, and moisture resistance, and a circuit substrate, particularly a metal-based circuit substrate, which has excellent adhesion between a metal plate and a conductive circuit, excellent stress relaxation properties, and does not cause abnormalities when cracks occur in the solder or in the vicinity thereof even when subjected to rapid heating / cooling. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-266535 A Summary of the Invention [Problem to be solved by the invention]

[0005] The above-mentioned metal base substrate is required to ensure insulation reliability even when a higher voltage than before is applied, and it is particularly desired to improve insulation reliability under high temperature or high temperature and high humidity environments.

[0006] Therefore, an object of one aspect of the present invention is to provide a metal base substrate that has excellent insulation reliability against high voltages in high temperature or high temperature and high humidity environments. [Means for solving the problem]

[0007] The inventors have discovered that by combining an inorganic filler with a specific amount of a copolymer having a specific structure in a composition for forming an insulating layer of a metal base substrate, a metal base substrate having excellent insulating reliability against high voltages in high temperature or high temperature / high humidity environments can be obtained.

[0008] That is, in some aspects, the present invention provides the following [1] to

[10] . [1] A composition comprising an inorganic filler, and a copolymer having (meth)acrylic monomer units A having an anionic group, (meth)acrylic monomer units B having a cationic group, and (meth)acrylic monomer units C other than the (meth)acrylic monomer units A and the (meth)acrylic monomer units B, wherein the content of the copolymer is 0.01 to 10 parts by mass per 100 parts by mass of the inorganic filler. [2] The composition according to [1], wherein the anionic group includes one or more groups selected from the group consisting of a carboxy group, a phosphate group, and a phenolic hydroxy group. [3] The composition according to [1] or [2], wherein the (meth)acrylic monomer unit A further has an electron-withdrawing group bonded to the anionic group. [4] The composition according to any one of [1] to [3], wherein the cationic group includes one or more groups selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium base. [5] The composition according to any one of [1] to [4], wherein the (meth)acrylic monomer unit B further has an electron-donating group bonded to the cationic group. [6] The composition according to any one of [1] to [5], wherein the (meth)acrylic monomer unit C contains one or more selected from the group consisting of an oxyalkylene group, a siloxane group, a hydrocarbon group, and a phosphate ester group. [7] The composition according to any one of [1] to [6], further comprising a resin. [8] The composition according to [7], further comprising a curing agent for curing the resin. [9] A cured body of the composition described in [8].

[10] A metal base substrate comprising a metal plate, the cured body according to [9] arranged on the metal plate, and a metal foil arranged on the cured body. Effect of the Invention

[0009] According to one aspect of the present invention, a metal base substrate having excellent insulation reliability against high voltages in high temperature or high temperature and high humidity environments can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a metal base substrate. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing another embodiment of the metal base substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail, but the present invention is not limited thereto.

[0012] One embodiment of the present invention is a composition containing an inorganic filler and a copolymer.

[0013] The inorganic filler may be, for example, a known inorganic filler used in applications requiring insulation and thermal conductivity. The inorganic filler may include, for example, one or more selected from the group consisting of aluminum oxide (alumina), silicon oxide, silicon nitride, boron nitride, aluminum nitride, and magnesium oxide, and from the viewpoint of further improving insulation reliability under high humidity environment, may include one or more selected from the group consisting of aluminum oxide, silicon oxide, silicon nitride, boron nitride, and aluminum nitride, and may include one or more selected from the group consisting of aluminum oxide, boron nitride, and aluminum nitride.

[0014] The shape of the inorganic filler may be, for example, particulate, scaly, polygonal, etc. The average particle size of the inorganic filler may be 0.05 μm or more, 0.1 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, or 30 μm or more from the viewpoint of improving thermal conductivity, and may be 200 μm or less, 150 μm or less, 100 μm or less, or 80 μm or less from the viewpoint of further improving insulation. In this specification, the average particle size of the inorganic filler means the d50 diameter in the volume-based particle size distribution of the inorganic filler. The volume-based particle size distribution of the inorganic filler is measured by a laser diffraction particle size distribution measuring device.

[0015] The inorganic filler may contain two or more inorganic fillers having different average particle sizes. For example, the inorganic filler may contain a first inorganic filler having an average particle size of 25 μm or more and a second inorganic filler having an average particle size of 4 μm or less. With such an inorganic filler, the gaps between the first inorganic fillers are filled with the second inorganic filler, thereby increasing the packing density and contributing to improving the thermal conductivity.

[0016] The average particle size of the first inorganic filler may be 30 μm or more or 40 μm or more, and 200 μm or less or 150 μm or less. The average particle size of the second inorganic filler may be 3.5 μm or less or 3 μm or less, and 0.05 μm or more or 0.1 μm or more.

[0017] The content of the inorganic filler may be 20 volume % or more, 30 volume % or more, 40 volume % or more, or 50 volume % or more based on the total volume of the composition from the viewpoint of improving thermal conductivity. The content of the inorganic filler may be 80 volume % or less, 70 volume % or less, or 60 volume % or less based on the total volume of the composition from the viewpoint of further improving insulating properties, and may be preferably 55 volume % or less from the viewpoint of obtaining a metal base substrate having even more excellent insulating reliability against high voltage under high temperature or high temperature and high humidity environments.

[0018] The copolymer has a (meth)acrylic monomer unit A having an anionic group (hereinafter also referred to as "unit A", and a monomer that gives unit A is also referred to as "monomer A"); a (meth)acrylic monomer unit B having a cationic group (hereinafter also referred to as "unit B", and a monomer that gives unit B is also referred to as "monomer B"); and a (meth)acrylic monomer unit C other than the (meth)acrylic monomer unit A and the (meth)acrylic monomer unit B (hereinafter also referred to as "unit C", and a monomer that gives unit C is also referred to as "monomer C"). The copolymer may have a (meth)acrylic monomer unit (unit X) having both an anionic group and a cationic group. In this case, unit X is considered to correspond to unit A and unit B. In other words, a copolymer having unit X is considered to have both unit A and unit B.

[0019] In this specification, "monomer" means a monomer having a polymerizable group before polymerization. "Monomer unit" means a structural unit derived from the monomer and constituting a copolymer. "(Meth)acrylic monomer" means a monomer having a (meth)acryloyl group. "(Meth)acrylic monomer" means an acrylic monomer and the corresponding methacrylic monomer, and similar expressions such as "(meth)acryloyl group" have the same meaning.

[0020] The copolymer has one or more types of each of the unit A, the unit B, and the unit C. In one embodiment, the copolymer may have only the unit A, the unit B, and the unit C. The copolymer may be a random copolymer or a block copolymer. The monomer A, the monomer B, and the monomer C may each be a monomer having one (meth)acryloyl group (monofunctional (meth)acrylic monomer), or a monomer having two or more (meth)acryloyl groups (polyfunctional (meth)acrylic monomer), and are preferably monofunctional (meth)acrylic monomers.

[0021] The anionic group contained in the unit A is, for example, at least one selected from the group consisting of a carboxy group, a phosphoric acid group, a phenolic hydroxy group, and a sulfonic acid group. From the viewpoint of further improving the dispersibility of the inorganic filler, the anionic group is preferably at least one selected from the group consisting of a carboxy group, a phosphoric acid group, and a phenolic hydroxy group.

[0022] From the viewpoint of further improving the dispersibility of the inorganic filler, the unit A preferably further has an electron-withdrawing group bonded to the anionic group. The electron-withdrawing group has the effect of stabilizing the anion of the anionic group. Examples of the electron-withdrawing group include a halogen group (also called a halogeno group). Examples of the anionic group bonded to an electron-withdrawing group include a group in which a halogen group is bonded to the carbon atom at the α-position of a carboxy group.

[0023] The unit A may not have an electron donating group bonded to the anionic group. The electron donating group may destabilize the anion of the anionic group. An example of the electron donating group is a methyl group.

[0024] Examples of the monomer A include acrylic acid, methacrylic acid, acid phosphooxypropyl methacrylate, acid phosphooxypolyoxyethylene glycol monomethacrylate, acid phosphooxypolyoxypropylene glycol monomethacrylate, phosphoric acid modified epoxy acrylate, 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, 4-hydroxyphenyl acrylate, 4-hydroxyphenyl methacrylate, 2-methacryloyloxyethyl succinic acid, 2-acrylamido-2-methylpropanesulfonic acid, etc. From the viewpoint of further improving the dispersibility of the inorganic filler, the monomer A is preferably one or more selected from the group consisting of acrylic acid, 2-methacryloyloxyethyl phosphate, 4-hydroxyphenyl methacrylate, and 2-acrylamido-2-methylpropanesulfonic acid, more preferably acrylic acid.

[0025] The cationic group contained in the unit B is, for example, one or more selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt group. From the viewpoint of further improving the dispersibility of the inorganic filler, the cationic group is preferably a tertiary amino group.

[0026] From the viewpoint of further improving the dispersibility of the inorganic filler, the unit B preferably further has an electron donating group bonded to the cationic group. The electron donating group has the effect of stabilizing the cation of the cationic group. An example of the electron donating group is a methyl group. An example of the cationic group bonded to an electron donating group is a group in which a methyl group is bonded to the carbon atom at the α-position of an amino group.

[0027] The unit B may not have an electron-withdrawing group bonded to the cationic group. The electron-withdrawing group may destabilize the cation of the cationic group. An example of the electron-withdrawing group is a carboxy group.

[0028] Examples of the monomer B include 1-aminoethyl acrylate, 1-aminopropyl acrylate, 1-aminoethyl methacrylate, 1-aminopropyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, t-butylaminoethyl (meth)acrylate, dimethylaminoethyl methacrylate quaternary salt, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, dimethylaminoethyl acrylate benzyl chloride quaternary salt, etc. From the viewpoint of further improving the dispersibility of the inorganic filler, the monomer B is preferably one or more selected from the group consisting of 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate and 2,2,6,6-tetramethyl-4-piperidyl methacrylate, more preferably 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate.

[0029] Monomer C is a (meth)acrylic monomer that does not contain either a cationic group or an anionic group. Monomer C may have an amphipathic group, a hydrophobic group, or a hydrophilic group in addition to a (meth)acryloyl group. That is, unit C may have an amphipathic group, a hydrophobic group, or a hydrophilic group. Examples of the amphipathic group include an oxyalkylene group. Examples of the hydrophobic group include a siloxane group and a hydrocarbon group. Examples of the hydrophilic group include a phosphate ester group. Note that the hydrocarbon group here does not include a methyl group that constitutes a methacryloyl group (hereinafter, the same applies to the hydrocarbon group in monomer C and unit C).

[0030] From the viewpoint of affinity or compatibility between the copolymer and the resin when the composition further contains a resin, the unit C has one or more types selected from the group consisting of an oxyalkylene group, a siloxane group, and a hydrocarbon group, and more preferably has one or more types selected from the group consisting of a siloxane group and a hydrocarbon group.

[0031] Examples of the (meth)acrylic monomer having an oxyalkylene group include ethoxycarbonylmethyl (meth)acrylate, phenol ethylene oxide modified (meth)acrylate, phenol (ethylene oxide 2 mol modified) (meth)acrylate, phenol (ethylene oxide 4 mol modified) (meth)acrylate, paracumylphenol ethylene oxide modified (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, nonylphenol (ethylene oxide 4 mol modified) (meth)acrylate, nonylphenol (ethylene oxide 8 mol modified) (meth)acrylate, nonylphenol (propylene oxide 2.5 mol modified) acrylate, 2-ethylhexylcarbitol (meth)acrylate, ethylene oxide modified phthalic acid (meth)acrylate, ethylene oxide modified succinic acid (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate.

[0032] Examples of (meth)acrylic monomers having siloxane groups include α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane. Examples of (meth)acrylic monomers having hydrocarbon groups include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, and methoxylated cyclodecatriene (meth)acrylate.

[0033] An example of the (meth)acrylic monomer having a phosphate group is (meth)acryloyloxyethyl dialkyl phosphate.

[0034] In addition to the above, the monomer C may be, for example, a (meth)acrylic monomer having a hydroxy group. Examples of the (meth)acrylic monomer having a hydroxy group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate.

[0035] Monomer C may be, for example, a (meth)acrylic monomer having an amide bond. Examples of the (meth)acrylic monomer having an amide bond include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, diacetone(meth)acrylamide, and acryloylmorpholine.

[0036] Monomer C may be, for example, a polyfunctional (meth)acrylic monomer. Examples of polyfunctional (meth)acrylic monomers include 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexadiol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, 2-ethyl-2-butyl-propanediol (meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, 2-(1,2-cyclohexacarboximide)ethyl (meth)acrylate, hexanediol di(meth)acrylate, and polyfunctional (meth)acrylate having a bisphenol structure.

[0037] The content of the unit A may be 0.03 mol% or more, 0.1 mol% or more, 0.5 mol% or more, 1 mol% or more, 2 mol% or more, 3 mol% or more, 4 mol% or more, or 5 mol% or more, and may be 70 mol% or less, 60 mol% or less, 50 mol% or less, 40 mol% or less, 30 mol% or less, 20 mol% or less, or 15 mol% or less, based on 100 mol% of the total of all monomer units contained in the copolymer. When the content of the unit A is 0.03 mol% or more, the dispersibility of the inorganic filler tends to be improved. When the content of the unit A is 70 mol% or less, the viscosity of the composition is further reduced, and the handleability of the composition tends to be further improved.

[0038] The content of the unit B may be 0.02 mol% or more, 0.05 mol% or more, 0.07 mol% or more, or 0.1 mol% or more, and may be 20 mol% or less, 10 mol% or less, 5 mol% or less, 3 mol% or less, or 1 mol% or less, based on 100 mol% of the total of the units A, B, and C. The content of the unit B may be within the above range based on 100 mol% of the total of all monomer units contained in the copolymer. When the content of the unit B is 0.02 mol% or more, the affinity of the copolymer to the inorganic filler tends to be better. When the content of the unit B is 20 mol% or less, the viscosity of the composition tends to be lowered, and the handleability of the composition tends to be improved.

[0039] The content of the unit C may be 10 mol% or more, 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and may be 99.8 mol% or less, 99 mol% or less, 98 mol% or less, 97 mol% or less, or 96 mol% or less, based on 100 mol% of the total of all monomer units contained in the copolymer. When the content of the unit C is 10 mol% or more, the viscosity of the composition is further reduced, and the handleability of the composition tends to be further improved. When the content of the unit C is 99.8 mol% or less, the affinity of the copolymer to the inorganic filler tends to be better.

[0040] The total content of the unit A and the unit B may be 0.05 mol% or more, 0.2 mol% or more, 1 mol% or more, 2 mol% or more, 3 mol% or more, 4 mol% or more, or 5 mol% or more, and may be 90 mol% or less, 80 mol% or less, 70 mol% or less, 60 mol% or less, 50 mol% or less, 40 mol% or less, 30 mol% or less, 20 mol% or less, or 10 mol% or less, based on the total of all monomer units contained in the copolymer (100 mol%). When the total content of the unit A and the unit B is 0.05 mol% or more, the dispersibility of the inorganic filler tends to be further improved. When the total content of the unit A and the unit B is 90 mol% or less, the handleability of the composition tends to be further improved.

[0041] The molar ratio of units A to units B (units A / units B) may be 0.01 or more, 0.9 or more, 1 or more, 5 or more, 10 or more, 20 or more, or 30 or more, and may be 200 or less, 150 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, or 10 or less. When the molar ratio of units A to units B is within the above range, the dispersibility of the inorganic filler tends to be further improved.

[0042] The weight average molecular weight of the copolymer may be 1,000 or more, 5,000 or more, 7,000 or more, 10,000 or more, 20,000 or more, 30,000 or more, 40,000 or more, or 50,000 or more, and may be 1,000,000 or less, 500,000 or less, 300,000 or less, 100,000 or less, 90,000 or less, 80,000 or less, 70,000 or less, or 60,000 or less. By having the weight average molecular weight of the copolymer be 1,000 or more, even if the composition is stored for a long time under a high temperature environment, the dispersibility of the inorganic filler can be maintained and the hardness of the composition can be suppressed from increasing. In addition, the shape retention of the composition is improved, and the composition is prevented from slipping or dripping when applied to an inclined or vertical surface. By making the weight-average molecular weight of the copolymer 1,000,000 or less, the viscosity of the composition is further reduced, and the handleability of the composition tends to be further improved. The weight-average molecular weight of the copolymer is determined as the weight-average molecular weight converted into standard polystyrene using the GPC (gel permeation chromatography) method.

[0043] The content of the copolymer is 0.1 to 10 parts by mass relative to 100 parts by mass of the inorganic filler. When the content of the copolymer is within this range, when an insulating layer of a metal base substrate is formed using the composition, a metal base substrate having excellent insulating reliability against high voltages in high temperature or high temperature and high humidity environments can be obtained.

[0044] The lower limit of the copolymer content may be preferably 0.5 parts by mass or more or 1 part by mass or more, more preferably 2 parts by mass or more, 2.5 parts by mass or more, 3 parts by mass or more, 4 parts by mass or more, or 5 parts by mass or more, relative to 100 parts by mass of inorganic filler, from the viewpoint of obtaining a metal base substrate having even more excellent insulation reliability against high voltage under high temperature or high temperature and high humidity environment. The upper limit of the copolymer content may be preferably 9.5 parts by mass or less or 9 parts by mass or less, more preferably 8 parts by mass or less, 7.5 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, or 5 parts by mass or less, relative to 100 parts by mass of inorganic filler, from the viewpoint of obtaining a metal base substrate having even more excellent insulation reliability against high voltage under high temperature or high temperature and high humidity environment.

[0045] The composition may further contain a resin. The resin here is different from the copolymer described above. The resin is preferably a thermosetting resin. Examples of the thermosetting resin include silicone resin, epoxy resin, phenol resin, cyanate resin, melamine resin, urea resin, thermosetting polyimide resin, and unsaturated polyester resin. The resin is preferably an epoxy resin. The resin is used alone or in combination of two or more kinds.

[0046] From the viewpoint of further improving the insulating property, the resin content may be 20 volume % or more, 30 volume % or more, or 40 volume % or more based on the total volume of the composition, and from the viewpoint of improving the thermal conductivity, the resin content may be 80 volume % or less, 70 volume % or less, 60 volume % or less, or 50 volume % or less based on the total volume of the composition.

[0047] When the composition contains a resin, the composition may further contain a curing agent that cures the resin. The curing agent is appropriately selected according to the type of the resin. For example, when the resin is an epoxy resin, the curing agent may be an amine-based resin, an acid anhydride-based resin, or a phenol-based resin. The curing agent may be used alone or in combination of two or more kinds.

[0048] The content of the curing agent may be 1 vol % or more and 10 vol % or less based on the total volume of the composition.

[0049] The composition may further contain other components, such as, for example, a curing accelerator, a coupling agent, a leveling agent, an antioxidant, an antifoaming agent, a wetting agent, and a stabilizer.

[0050] The composition is obtained by mixing the inorganic filler and the copolymer (and further the resin, curing agent, and other components used as necessary). The mixing may be performed using, for example, a planetary mixer, a universal mixer, a kneader, a hybrid mixer, or the like.

[0051] The copolymer is obtained by polymerizing the monomer A, the monomer B, and the monomer C by a known polymerization method. Examples of the polymerization method include radical polymerization and anionic polymerization. The polymerization method is preferably radical polymerization.

[0052] The polymerization initiator used in the radical polymerization may be a thermal polymerization initiator or a photopolymerization initiator. Examples of the thermal polymerization initiator include azo compounds such as azobisisobutyronitrile, and organic peroxides such as benzoyl peroxide, tert-butyl hydroperoxide, and di-tert-butyl peroxide. Examples of the photopolymerization initiator include benzoin derivatives. The polymerization initiator may be a known polymerization initiator used in living radical polymerization such as ATRP and RAFT.

[0053] The polymerization conditions can be appropriately adjusted depending on the type of monomer, polymerization initiator, etc. When the copolymer is a random copolymer, the monomers may be mixed in advance and polymerized. When the copolymer is a block copolymer, the monomers may be added sequentially to the polymerization system.

[0054] The composition described above, particularly when the composition contains a resin and a curing agent, is cured before use. That is, one embodiment of the present invention is a cured product of the composition described above. The cured product may be in a semi-cured state (B stage) or a completely cured state (C stage).

[0055] The cured product can be obtained, for example, by subjecting the above-mentioned composition to a heat treatment to cure it. The conditions of the heat treatment (heating temperature, heating time, etc.) are appropriately set depending on the types of resin and curing agent, the desired cured state, etc. The heat treatment can be performed in one step or two steps.

[0056] The cured product may be, for example, in the form of a sheet. The sheet-shaped cured product may be obtained, for example, by applying the above-mentioned composition onto a substrate and heating (and pressing as necessary). The sheet-shaped cured product may be a semi-cured B-stage sheet or a completely cured C-stage sheet.

[0057] The above-mentioned composition and cured product are preferably used for forming an insulating layer of a metal base substrate. That is, the above-mentioned composition and cured product can be called a composition for metal base substrates and a cured product for metal base substrates, respectively.

[0058] Fig. 1 is a schematic cross-sectional view showing one embodiment of a metal base substrate. As shown in Fig. 1, a metal base substrate 10A according to one embodiment includes a metal plate 1, a cured body (a cured body of the above-mentioned composition) 2 arranged on the metal plate, and a metal foil 3A arranged on the cured body 2. In this metal base substrate 10A, the metal plate 1 and the metal foil 3A are separated by the cured body 2 and are electrically insulated from each other. In other words, the cured body 2 functions as an insulating layer.

[0059] Examples of metal materials constituting the metal plate 1 include aluminum, aluminum alloys, copper, copper alloys, iron, and stainless steel. The metal plate 1 may be made of one type of metal material, or may be made of two or more types of metal materials. The metal plate 1 may have a single-layer structure or a multi-layer structure.

[0060] Examples of metal materials constituting the metal foil 3A include copper, aluminum, and nickel. The metal foil 3A may be made of one type of metal material, or may be made of two or more types of metal materials. The metal foil 3A may have a single-layer structure or a multi-layer structure.

[0061] The thickness of the metal plate 1 may be, for example, 0.5 mm or more and 3 mm or less. The thickness of the cured body 2 may be, for example, 50 μm or more and 300 μm or less. The thickness of the metal foil 3A may be, for example, 5 μm or more and 1 mm or less.

[0062] In the above embodiment, the metal foil 3A is disposed on almost the entire surface of the cured body 2, but in another embodiment, the metal foil may be disposed on only a portion of the cured body 2. Fig. 2 is a schematic cross-sectional view showing another embodiment of the metal base substrate. As shown in Fig. 2, the metal base substrate 10B according to the other embodiment includes a metal plate 1, a cured body (a cured body of the above-mentioned composition) 2 disposed on the metal plate, and a metal foil 3B disposed on the cured body 2.

[0063] In this metal base substrate 10B, the metal foil 3B is processed (e.g., etched) into a predetermined pattern to form a circuit. In other words, this metal base substrate 10B can be said to include a metal plate 1, a hardened body 2 disposed on the metal plate, and a metal circuit disposed on the hardened body 2. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0065] <Synthesis of copolymer> The monomers used in the synthesis of the copolymer are shown below. ((Meth)acrylic monomer A having an anionic group) Acrylic acid (manufactured by Toagosei Co., Ltd.) ((Meth)acrylic monomer B having a cationic group) 1,2,2,6,6-Pentamethyl-4-piperidyl methacrylate (ADEKA Corporation "ADEKA STAB LA-82") ((Meth)acrylic monomer C) Benzyl methacrylate ("Light Ester BZ" manufactured by Kyoeisha Chemical Co., Ltd.)

[0066] First, 100 parts by mass of (meth)acrylic monomers having the monomer composition (mol%) shown in Table 1 were added to an autoclave equipped with a stirrer. Next, 0.5 parts by mass of azobisisobutyronitrile (manufactured by Tokyo Chemical Industry Co., Ltd.) as a polymerization initiator and 1000 parts by mass of a mixed solution of toluene (special grade reagent) and 2-propanol (special grade reagent) (toluene:2-propanol=7:3 (volume ratio)) as a solvent were added to a total of 100 parts by mass of the (meth)acrylic monomers, and the inside of the autoclave was replaced with nitrogen. Thereafter, the autoclave was heated at 65°C in an oil bath for 20 hours to carry out radical polymerization. After the polymerization was completed, the mixture was degassed under reduced pressure at 120°C for 1 hour to obtain copolymers 1 to 5.

[0067] The polymerization rate was 98% or more when analyzed by gas chromatography based on 100% of the monomer charge, which suggested that the ratio of each monomer unit in the copolymer was approximately the same as the monomer charge ratio.

[0068] The weight average molecular weights of the obtained copolymers 1 to 5 were determined as standard polystyrene-equivalent weight average molecular weights by GPC (gel permeation chromatography). The results are shown in Table 1. The measurement conditions were as follows. High-speed GPC equipment: Tosoh Corporation "HLC-8020" Columns: One Tosoh "TSK guardcolumn MP(xL)" 6.0mmID x 4.0cm, and two Tosoh "TSK-GELMULTIPOREHXL-M" 7.8mmID x 30.0cm (16,000 theoretical plates), for a total of three (total theoretical plates: 32,000) Developing solvent: Tetrahydrofuran Detector: RI (Differential Refractometer)

[0069] [Table 1]

[0070] <Preparation of Composition> Example 1 The resin used was naphthalene-type epoxy resin HP-4032D (DIC Corporation, specific gravity 1.2 g / cm 3 ) 42.3 volume% and phenol novolac resin VH-4150 (DIC Corporation, specific gravity 1.1 g / cm) as a hardener. 3 50.5% by volume of boron nitride filler (manufactured by Denka Corporation, FP-40, average particle size 40 μm) as inorganic filler (1), 1.0% by volume of copolymer 1, imidazole compound 1B2PZ (manufactured by Shikoku Chemical Industry Co., Ltd., specific gravity 1.1 g / cm) as a curing accelerator, and 5.7% by volume of 1.0% by volume of copolymer 1 were mixed and stirred at 170° C. to dissolve the curing agent in the resin. 3 ) was mixed and stirred for 15 minutes in a planetary mixer to prepare a composition.

[0071] <Preparation of hardened body> The obtained composition was applied onto a 0.038 mm thick polyethylene terephthalate (PET) film so that the thickness after curing would be 0.20 mm, and then heated and dried at 100°C for 50 minutes, thereby producing a semi-cured product (B-stage sheet).

[0072] <Preparation of metal base substrate> The obtained cured product (B-stage sheet) was peeled off from the PET film and placed on the roughened surface of a metal plate (2.0 mm thick copper plate). Next, the roughened surface of a metal foil (0.5 mm thick copper foil) was placed on the cured product, and the cured product was heated and cured at 180°C for 410 minutes while applying a surface pressure of 10 MPa using a press machine.

[0073] Next, after masking predetermined positions with an etching resist, the copper foil was etched using a sulfuric acid-hydrogen peroxide mixed solution as an etching solution. The etching resist was removed, and the copper foil was washed and dried to obtain a metal base substrate with a circular electrode (copper foil) with a diameter of 20 mm.

[0074] (Examples 2 to 13 and Comparative Examples 1 to 2) Except for changing the composition as shown in Tables 2 and 3, the composition, the cured body, and the metal base substrate were prepared in the same manner as in Example 1. In Tables 2 and 3, the inorganic filler (2) and the inorganic filler (3) are as follows. Inorganic Filler(2) Alumina filler (Denka, DAS-45, average particle size 40 μm) Inorganic Filler(3) Aluminum nitride filler (Denka, AlN-32, average particle size 32 μm)

[0075] [Evaluation of insulation reliability in high temperature environments] A high-temperature, high-voltage bias test (Vt) was conducted on the obtained metal base substrate under test conditions of applying a DC voltage of 10 kV between the metal foil and metal plate in a 125°C environment. The endurance time was determined as the time from the start of voltage application to the point at which the leakage current value measured by the voltage withstand tester reached 10 mA or more. Endurance times of 200 minutes or more were rated A, times less than 200 minutes but 100 minutes or more were rated B, and times less than 100 minutes were rated C. If the evaluation was A or B, it can be said that the metal base substrate has excellent insulation reliability in a high-temperature environment. The results are shown in Tables 2 and 3.

[0076] [Evaluation of insulation reliability under high temperature and high humidity conditions] A high temperature, high voltage bias test (THB) was conducted on the obtained metal base substrate under test conditions of applying a DC voltage of 1.2 kV between the metal foil and metal plate in an environment of 85°C and 85% humidity. The endurance time was determined as the time from the start of voltage application to the point at which the leakage current value measured by the voltage withstand tester reached 10 mA or more. Endurance times were rated as A for 250 hours or more, B for less than 250 hours but 100 hours or more, and C for less than 100 hours. If the evaluation was A or B, it can be said that the metal base substrate has excellent insulation reliability in a high temperature, high humidity environment. The results are shown in Tables 2 and 3.

[0077] [Table 2]

[0078] [Table 3] [Explanation of symbols]

[0079] 1...metal plate, 2...hardened body, 3A, 3B...metal foil, 10A, 10B...metal base substrate.

Claims

1. An inorganic filler having an average particle size of 10 μm or more and 80 μm or less, A copolymer having a (meth)acrylic monomer unit A having an anionic group, a (meth)acrylic monomer unit B having a cationic group, and a (meth)acrylic monomer unit C having neither a cationic group nor an anionic group and having a hydrocarbon group; A resin different from the copolymer; Contains the (meth)acrylic monomer unit C is one or more monomer units selected from the group consisting of benzyl methacrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and isobornyl (meth)acrylate; the content of the unit A is 0.1 mol % or more, the content of the unit B is 0.1 mol % or more, and the content of the unit C is 80 mol % or more, based on 100 mol % of the total of all monomer units contained in the copolymer; The content of the inorganic filler is 20% by volume or more and 55% by volume or less based on the total volume of the composition, The content of the copolymer is 2 to 8 parts by mass relative to 100 parts by mass of the inorganic filler, The content of the resin is 20% by volume or more based on the total volume of the composition.

2. The composition according to claim 1 , wherein the anionic group comprises at least one selected from the group consisting of a carboxy group, a phosphate group, and a phenolic hydroxy group.

3. The composition according to claim 1 or 2, wherein the (meth)acrylic monomer unit A further has an electron-withdrawing group bonded to the anionic group.

4. The composition according to any one of claims 1 to 3, wherein the cationic group comprises at least one selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt group.

5. The composition according to any one of claims 1 to 4, wherein the (meth)acrylic monomer unit B further has an electron donating group bonded to the cationic group.

6. The composition according to any one of claims 1 to 5, further comprising a hardener for hardening the resin.

7. A cured product of the composition according to claim 6.

8. A metal plate; The hardened body according to claim 7 , which is disposed on the metal plate; A metal foil disposed on the cured body; A metal base substrate comprising:

Citation Information

Patent Citations

  • Composition for circuit board and circuit board using the same

    JP2008266535A

  • Resin composition, resin sheet, resin sheet with metal foil, resin cured article sheet, semiconductor device for power source or for light source

    JP2016104862A

  • Epoxy resin composition, semi-cured epoxy resin composition and cured epoxy resin composition, and resin sheet, prepreg, laminate sheet, metal substrate, wiring board and power semiconductor device, using these

    JP2016155985A

  • Epoxy resin composition, semi-cured epoxy resin composition, cured epoxy resin composition, resin sheet, prepreg, laminate, metal substrate, wiring board, method for producing semi-cured epoxy resin composition, and method for producing cured epoxy resin composition

    JP2017160440A

  • Heat-conductive resin composition, resin sheet, resin-clad metal foil, cured resin sheet, and heat-dissipating member

    WO2012039324A1